Museum specimens of terrestrial vertebrates are sensitive indicators of environmental change in the Anthropocene. (19th November 2018) - Schmitt, C. Jonathan; Cook, Joseph A.; Zamudio, Kelly R.; Edwards, Scott V.
Abstract : Natural history museums and the specimen collections they curate are vital scientific infrastructure, a fact as true today as it was when biologists began collecting and preserving specimens over 200 years ago. The importance of museum specimens in studies of taxonomy, systematics, ecology and evolutionary biology is evidenced by a rich and abundant literature, yet creative and novel uses of specimens are constantly broadening the impact of natural history collections on biodiversity science and global sustainability. Excellent examples of the critical importance of specimens come from their use in documenting the consequences of environmental change, which is particularly relevant considering the alarming rate at which we now modify our planet in the Anthropocene. In this review, we highlight the important role of bird, mammal and amphibian specimens in documenting the Anthropocene and provide examples that underscore the need for continued collection of museum specimens. This article is part of the theme issue 'Biological collections for understanding biodiversity in the Anthropocene'.